A Comparative Study of the Impact of the Covid-19 Pandemic on Mental Health, Healthcare Access, and Pain Levels of Patients with Chronic Pain from Spring 2020 to Spring 2021 - Smyrnioti ME; Batistaki C; Yotsidi V; Matsota P (Dove Medical Press, 2024)
Maria Eleni Smyrnioti,1 Chrysanthi Batistaki,1 Vasiliki Yotsidi,2 Paraskevi Matsota1 1 2nd Department of Anesthesiology, School of Medicine, National and Kapodistrian University of Athens, Pain Management Unit, "Attikon" Hospital, Athens, Greece; 2Department of Psychology, Panteion University of Social and Political Sciences, Athens, GreeceCorrespondence: Maria Eleni Smyrnioti, 2nd Department of Anaesthesiology, Pain Management Unit, Attikon University Hospital, 1 Rimini Street, Athens, 12462, Greece, Tel +30 6947526444, Fax +302105832371, Email Marilena_smyrnioti@yahoo.grPurpose: The short-term impact of the Covid-19 pandemic on patients with chronic pain has been under the microscope since the beginning of the pandemic. This time-lag design study aimed to track changes in pain levels, access to care, mental health, and well-being of Greek chronic pain patients within the first year of the Covid-19 pandemic.Patients and Methods: 101 and 100 chronic pain patients were contacted during the Spring of 2020 and 2021, respectively. A customized questionnaire was used to evaluate the perceived impact of the pandemic on pain levels and healthcare access. Psychological responses, personality characteristics, and overall well-being were evaluated using the Depression, Anxiety, and Stress Scale (DASS-42), the Ten-Item Personality Index (TIPI) and the Personal Wellbeing Index (PWI).Results: The perceived effect of the pandemic and the Covid-related restrictions affected significantly access to healthcare, pain levels and quality of life. Differences were detected in the PWI sub-scales regarding Personal Safety, Sense of Community-Connectedness, Future Security, Spirituality-Religiousness, and General Life Satisfaction. Marital status, parenthood, education and place of residence were associated with differences in pain levels, emotional and psychological responses.Conclusion: Changes in chronic pain levels, emotional responses, and overall well-being took place throughout the year. Also, an evident shift took place in the care delivery system. Both tendencies disclose an ongoing adaptation process of chronic pain patients and healthcare services that needs further monitoring.Keywords: healthcare access, anxiety, stress, resilience, personality traits, emotional wellbeing